De novo assembly of the common bean transcriptome using short reads for the discovery of drought-responsive genes. - Jing Wu (Public Library of Science (PLoS), 2014)
The common bean (Phaseolus vulgaris L.) is one of the most important food legumes, far ahead of other legumes. The average grain yield of the common bean worldwide is much lower than its potential yields, primarily due to drought in the field. However, the gene network that mediates plant responses to drought stress remains largely unknown in this species. The major goals of our study are to identify a large scale of genes involved in drought stress using RNA-seq. First, we assembled 270 million high-quality trimmed reads into a non-redundant set of 62,828 unigenes, representing approximately 49 Mb of unique transcriptome sequences. Of these unigenes, 26,501 (42.2%) common bean unigenes had significant similarity with unigenes/predicted proteins from other legumes or sequenced plants. All unigenes were functionally annotated within the GO, COG and KEGG pathways. The strategy for de novo assembly of transcriptome data generated here will be useful in other legume plant transcriptome studies. Second, we identified 10,482 SSRs and 4,099 SNPs in transcripts. The large number of genetic markers provides a resource for gene discovery and development of functional molecular markers. Finally, we found differential expression genes (DEGs) between terminal drought and optimal irrigation treatments and between the two different genotypes Long 22-0579 (drought tolerant) and Naihua (drought sensitive). DEGs were confirmed by quantitative real-time PCR assays, which indicated that these genes are functionally associated with the drought-stress response. These resources will be helpful for basic and applied research for genome analysis and crop drought resistance improvement in the common bean.